## Related Questions

Solve the equation for y 2x+6y=13

2x+6y=13

Next, transfer 2x to the right side and it will look like this:

6y=13-2x

Now, divide both sides by 6, and it will look like this:

y=13-2x

--------

6

So, this is the final answer for y.

Hope this answers your question. Have a great day!

How to solve this problem 14-6= 10-6=?

**If ST = 21, SP = 3b – 11, and PT = b + 4, the value of b would be 14.**

I hope my answer has come to your help. God bless and have a nice day ahead!

Solve the inequality. y – 5 ≥ 11

Add 5 to the both sides,

y - 5 + 5 ≥ 11 + 5

**y ≥ 16**

Hope this helps!

## Use our writing service to score better and meet your deadlines

No matter what kind of academic paper you need, it is simple and secure to hire a writer for a price you can afford at StudyHawks. Save more time for yourself.

Solve the inequality. p – 9 < –9

p-9 < -9

p-9+9 < -9+9

p <0

Solve the inequality by adding. x – 7 > –11

x-7+7> -11+7

x> -4

**1) The answer is: [B]: r = 5 .**

**__________________________**

**Explanation:**

**___________**_______________

Given: 7r − 7 = 2r + 18 ; Round your answer to the nearest tenth, if necessary.

____________________________

Since "r" is the only variable given, let us assume we want to solve for "r" (instead of "x").

___________________________

→ Subtract "2r" from EACH SIDE of the equation; and & add "7" to EACH SIDE of the equation:

_____________

→ 7r − 7 − 2r + 7 = 2r + 18 − 2r + 7 ; to get: → 5r = 25 ;

_____________

→ Now, divide EACH SIDE of the equation by "5"; to isolate "r" on one side of the equation; and to solve for "r" :

______________

→ 5r / 5 = 25 / 5 → r = 5 → which is: "Answer choice: [B]".

_________________

**Let us check our answer, by plugging in "5" for "r" in the original equation:**

_________________

→ 7r − 7 = 2r + 18 ; → 7(5) − 7 =? 2(5) + 18? ;

______________________

→ 35 − 7 =? 10 + 18 ?; → 28 =? 28? Yes!

______________________

**2) The answer is: [D]: x = 2 .**

**_____________**

**Explanation:**

_____________

Given: 2x + 12 = 18 − x ; Solve for "x" (round to nearest tenth, if necessary).

_______________

→ Add "x" to EACH SIDE of the equation, & subtract "12" from EACH SIDE of the equation: → 2x + 12 + x − 12 = 18 − x + x − 12 ;

______________

→ To get: 3x = 6 ; → Divide EACH SIDE of the equation by "3";

to isolate "x" on one side of the equation; and to solve for "x":

_____________

→ 3x / 3 = 6 / 3 ; → x = 2 ; which is: "Answer choice: [D]".

______________

**Let us check our answer, by plugging in "2" for "x" in the original equation:**

________________

→ 2x + 12 = 18 − x ; → 2(2) + 12 =? 18 − 2 ?

________________

→ 4 + 12 =? 18 − 2 ? ; → 16 =? 16? Yes!

________________________________

**3) The answer is: [A]: x = -3 .**

**_____________**

**Explanation:**

________________

Given: 8x − 3 = 15x + 18 ; Solve for "x". Round your answer to the nearest tenth, if necessary.

_________________

→ Subtract "8x" from EACH SIDE of the equation, & add "3" to EACH SIDE of the equation:

_______________

→ 8x − 3 − 8x + 3 = 15x + 18 − 8x + 3 ; to get:

_______________

→ 0 = 7x + 21 ; → Subtract "21" from EACH SIDE of the equation;

_______________

→ 0 − 21 = 7x + 21 − 21 ; to get:

_______________

→ -21 = 7x ; Now divide EACH SIDE of the equation by "7";

to isolate "x" on one side of the equation; & to solve for "x":

_______________

→ = -21 / 7 = 7x / 7 ; → -3 = x ; which is "Answer choice: [A]."

**_________________**

**Let us check our answer, by plugging in "-3" for "x" in the original equation:**

________________

→ 8x − 3 = 15x + 18 ; → 8(-3) − 3 =? 15(-3) + 18 ?;

________________________

→ -24 − 3 =? -45 + 18 ? ; → -27 =? -27? Yes!

**___________________________**

**4) The answer is: [C]: y = 11 .**

**_____________**

**Explanation:**

**____________**

Given: 6y − 6 = 4y + 16 ; Solve for "y"; Round to the nearest tenth, if necessary.

____________

(Note: Since "y" is the only variable given; assume we are to solve for "y" instead of "x").

____________

→ Subtract "4y" from EACH SIDE of the equation, & add "6" to EACH SIDE of the equation; → 6y − 6 − 4y + 6 = 4y + 16 − 4y + 6 ; to get:

_______________

→ 2y = 22 ; Now, divide EACH SIDE of the equation by "2"; to isolate "y" one side of the equation; and to solve for "y" ;

_______________

→ 2y / 2 = 22 / 2 ; → y = 11 → which is "Answer choice: [C]".

**_______________________________**

**Let us check our answer, by plugging in "11" for "y" in the original equation:**

**___________________**

→ 6y − 6 = 4y + 16 ; → 6(11) − 6 =? 4(11) + 16 ?

_______________________

→ 66 − 6 =? 44 + 16 ? → 60 =? 60 ? Yes!

**__________________**

**5) The answer is: [B]: x = -11 .**

**_____________________**

**Explanation:**

**_________________**

Given: 3(x − 4) = 5(x + 2) ; Solve for "x". Round to the nearest tenth, if necessary.

**___________**

**→Note the "distributive property of multiplication":**

**_____________**

**a*(b + c) = ab + ac ; and: a*(b − c) = ab − ac ;**

**_______________**

→ Let us expand EACH SIDE of our given equation.

→Start with the "left-hand side":

____________

3(x − 4) = (3*x) − (3*4) = 3x − 12;

______________________________

→Now let us expand the "right-hand side" of the given equation:

____________

→ 5(x + 2) = (5*x) + (5*2) = 5x + 10 ;

______________

→Now, we can rewrite the original equation:

_______________

→ 3(x − 4) = 5(x + 2) ; by substituting the expanded values for EACH SIDE of the question: → 3x − 12 = 5x + 10 ;

__________________

→ Subtract "3x" from EACH SIDE of the equation; and add "12" to EACH SIDE of the equation: → 3x − 12 − 3x + 12 = 5x + 10 − 3x + 12 ; to get:

________________

→ 0 = 2x + 22; → Now subtract "22" from EACH SIDE of the equation:

______________

→ 0 − 22 = 2x + 22 − 22 ; to get: → -22 = 2x ;

__________

→ Divide EACH SIDE of the equation by "2"; to isolate "x" on one side of the equation; & to solve for "x" ;

_____________

→ -22 / 2 = 2x /2 ; → -11 = x ; which is "Answer choice: [B]".

______________

**Let us check our answer, by plugging in "-11" for "x" in the original equation:**

**___________**

→ 3(x − 4) = 5(x + 2) ; → 3(-11 − 4) =? 5(-11 + 2) ? ;

_______________________

→3(-15) =? 5(-9) ? ; → -45 =? -45 ? Yes!

**_____________________________________________**

**Hope these answers and explanations are helpful. Best of luck!**

Solve for w. 2w=12-4w Simplify your answer as much as possible.

2w=12-4w

Firstly, let's simplify, and divide all terms by 2:

w=6-2w

Now, we add 2w over to the other side:

3w=6

And finally, we divide both sides by 3:

w=2

Hope this helps!

n/7-8+8 < -11+8

n/7 < -3

n < -21

## Use our writing service to score better and meet your deadlines

No matter what kind of academic paper you need, it is simple and secure to hire a writer for a price you can afford at StudyHawks. Save more time for yourself.

K-X=V-W solve for the letter x

Mul -1 X = -(V-W) + K

X = -V + W + K

How many solutions does this system of equations have? exactly one none infinitely many exactly two

We need to see the graph in order to give you an answer

How was percent used to solve real-world problems

B. On Black Fridays, it would say 50% off, 30% off...

Solve the proportion 15t/5=2t +3 /6.

3t = 2t + 1/2

3t-2t = 1/2

t = 1/2

**So, your final answer is 1/2**

Hope this helps!

## Use our writing service to score better and meet your deadlines

No matter what kind of academic paper you need, it is simple and secure to hire a writer for a price you can afford at StudyHawks. Save more time for yourself.

p(x)/q(x) + r(x)/s(x) = [p(x)s(x) + q(x)r(x)] / [q(x)*s(x)].

The numerator and denominator of the sum will both be polynomials when fully expanded

Please help me solve this math problem

Ok, so when you're reading the bar graph, you can tell how many participants are in each group by looking at the y-axis. For example, there are 30 people under 17. There are 35 people aged 18-24, etc. The numbers on the y-axis you add up. So 30 (for under 17)+35(for 18-24), etc. Now, a percentage is basically a proportion. So the whole, which in this case is the total amount of people surveyed, will always be the denominator. Then the portion that we are trying to find, which in this case is the people surveyed under 17, will be the numerator. Hence, 30/140.

We have to do a change of variable.

cos x=t

Then, we have the next square equation.

t²+2t+1=0

We solve this square equation:

t=[-2⁺₋√(4-4)]/2=-1

if cos x=t then we have that:

cos x=-1

x=cos⁻¹ -1= π radians or 180º.

**Answer: x=π (in radians) or x=180º (in degrees).**

53p + 45h = 784.10

just a matter of subbing and solving...

53(h - 11) + 45h = 784.10

53h - 583 + 45h = 784.10

98h = 784.10 + 583

98h = 1367.10

h = 1367.10/98

h = 13.95

p = h - 11

p = 13.95 - 11

p = 2.95

so paperbacks (p) are 2.95 a piece and hardbacks (h) are 13.95 a piece

d = number of dimes

n + d = 59 {she has 59 coins total}

5n + 10d = 430 {value of coin times number of coins equals total value}

-5n - 5d = -295 {multiplied top equation by -5}

5n + 10d = 430 {bottom equation stays the same}

---------------

5d = 135 {added the two equations}

d = 27 {divided each side by 5}

n + d = 59 {first original equation}

n + 27 = 59 {substituted 27, in for d, into first original equation}

n = 32 {subtracted 27 from each side}

27 dimes

32 nickels

To answer the question, "what is the sum of the digits in the number of nickels?",

add 3 + 2

= 5

## Use our writing service to score better and meet your deadlines

Solve this problem for x and y 8x+4y=-12 and -9x+4y=-29

Result: {32y=12,-36y=29}

y = -4x +5

We can convert the first equation to the same form as the second (y=mx+b, or slope-intercept).

12x +3y = 12

3y = -12x +12

y = -4x +4

Comparing the simplified first equation y = -4x +4 to the second equation y = -4x + 5, we see that both have the same slope (m = -4), but different y-intercepts (b = 4, b = 5). This means they are parallel lines, or an inconsistent system. There are no solutions.

Solve the following system of equations 9x +2y=17

2y/2=17/2

y=8.5

9x+2(0)=17

9x/9=17/9

x=1.8

(1.8,8.5)

## Use our writing service to score better and meet your deadlines

The question asks you for the total populations of Cambridge, Massachusetts, and Boston, Massachusetts, altogether. That means you have to add the two given numbers together: 616,535 + 101,355 = 717,890. This, of course, is also what Hana did and got for the answer, therefore her statement is the correct one.

Hope I helped you! :)

Solve by elimination -3x+2y=10 -2x-y=-5

-3x + 2y = 10

-4x - 2y= -10

And then you minus

x = 20

Now you can substitute x in to one of the equations to find y:

-60 + 2y = 10

+ 60

2y = 70

÷ 2

y = 35

So your values are y = 35 and x = 20. Hope this helps!

Solve by elimination x+y=7 x-y=9

1.5x-2<10 how do you solve this

+ 2

5x < 12

÷ 5

x < 2.4

Hope this helped!

Solve the equation with the replacement set {–28, –8, 8, 28} |10 – x| = 18 –8, 8 –8, 28 8 –28